2015
DOI: 10.1007/s00231-015-1617-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of classical Fourier, SPL and DPL heat transfer model in biological tissues in presence of metabolic and external heat source

Abstract: In this paper, the temperature distribution in a finite biological tissue in presence of metabolic and external heat source when the surface subjected to different type of boundary conditions is studied. Classical Fourier, single-phase-lag (SPL) and dual-phase-lag (DPL) models were developed for bio-heat transfer in biological tissues. The analytical solution obtained for all the three models using Laplace transform technique and results are compared. The effect of the variability of different parameters such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Dombrovsky et al [6] derived an advanced thermal model for indirect heating strategy for laser induced hyperthermia. Kumar et al [29] compared the results obtained by PBHT, TWBHT, DPLBHT models with experimental results of Stolwijik and Hardy [30] and found that experimental data is close with DPLBHT model. Conventionally various numerical methods [31] such as finite difference method [32] , finite difference-decom position method [33] , finite volume method [5] , smoothed particle hydrodynamics method [34] or commercial softwares like COMSOL [24] are available in literature for solving bioheat equations.…”
Section: Introductionmentioning
confidence: 59%
“…Dombrovsky et al [6] derived an advanced thermal model for indirect heating strategy for laser induced hyperthermia. Kumar et al [29] compared the results obtained by PBHT, TWBHT, DPLBHT models with experimental results of Stolwijik and Hardy [30] and found that experimental data is close with DPLBHT model. Conventionally various numerical methods [31] such as finite difference method [32] , finite difference-decom position method [33] , finite volume method [5] , smoothed particle hydrodynamics method [34] or commercial softwares like COMSOL [24] are available in literature for solving bioheat equations.…”
Section: Introductionmentioning
confidence: 59%
“…It might be difficult to implement a classical analytical method for solving higher-order mixed partial derivatives. 37 Hence to deal with such situations ‘hybrid’ scheme may be effective. It is a combination of two different approaches either analytical-analytical or analytical-numerical.…”
Section: Mathematical Frameworkmentioning
confidence: 99%
“…Finding the analytical and numerical solutions of the DPL model ( 3) is one of the prime research areas in mathematical, biological, and thermal sciences. Some of the commonly employed numerical techniques for obtaining the solution of model (3) include the finite volume method [16], the Laplace transform method [17], the boundary element method [18], the finite difference-decomposition method [19], the Adomian decomposition method [20], and the B-spline method [21]. Some of the compelling alternatives of the aforementioned numerical techniques include the wavelet-based numerical methods.…”
Section: Introductionmentioning
confidence: 99%